Penguatan Kesadaran Pelajar dalam P4GN melalui KKN Mahasiswa Universitas Krisnadwipayana - Mishelei Loen; Yuaniko Paramitra; Diana Gustinya; Mulia Rahmah; Dhistianti Mei Rahmawantari; M. Kausar Maulana; Tatag Herbayu Latukismo; Nino Nopriandi Saleh; Arief Rachmawan Assegaf; Muhammad Harri; Laurimba Simorangkir (Jurnal PKM Manajemen Bisnis, 2026)
Drug abuse among adolescents remains a serious issue in Indonesia, as it threatens the quality of human resources and hampers the optimal utilization of the demographic bonus. This community service activity aimed to improve students’ understanding of types of drugs, their health and legal impacts, and their implications for future education and economic productivity. The Community Service Program (Kuliah Kerja Nyata/KKN) of Universitas Krisnadwipayana was conducted at SMK Yadika 6, MA Al Ihsan, and Sekolah Terbuka (Yayasan Intisyar Salam) from October 29 to November 24, 2025. The program was implemented by a team consisting of lecturers and students, totaling 11 participants, and involved 100 student participants from the target schools. The KKN activities employed an educational and participatory approach through several stages, including the delivery of educational materials, screening of educational videos, and interactive discussions. The results indicated an improvement in students’ understanding of various types of drugs and the risks associated with drug abuse, as well as active engagement and positive responses during the sessions. This program highlights the crucial role of educational institutions as the frontline in drug abuse prevention and demonstrates its potential as a sustainable preventive intervention model for students to support healthier, more productive future generations.